Sequence of maximal distance codes in graphs or other metric spaces - Charles Delorme (Electronic Journal of Graph Theory and Applications (EJGTA), 2013)
Given a subset C in a metric space E, its successor is the subset  s(C) of points at maximum distance from C in E. We study some properties of the sequence obtained by iterating this operation.  Graphs with their usual distance provide already typical examples.